Comparison of immunochemotherapy and chemotherapy alone in conversion therapy for locally advanced unresectable esophageal squamous cell carcinoma - Xu, Zhiyun; You, Zhenbing; Chen, Mengzhou; Zhang, Mingzhi; Shen, Cheng; Xu, Dafu; Xu, Keping; Tian, Wenze (Frontiers in Oncology, 2024)
Background The clinical value of preoperative immunochemotherapy and simple chemotherapy induction regimen in the conversion therapy of locally advanced unresectable esophageal squamous cell carcinoma (ESCC) is still unclear. Method Retrospective analysis was conducted on patients with unresectable cT4b stage ESCC who underwent conversion surgery in our hospital from January 2020 to December 2022. According to the preoperative induction treatment plan, they were divided into induction immunochemotherapy group (iICT group) and induction chemotherapy group (iCT group). The conversion surgery rate, R0 resection rate, radiological and pathological tumor responses, safety, and short-term survival outcomes were analyzed. Results The results showed that a total of 199 patients with cT4b locally advanced unresectable ESCC who underwent preoperative induction therapy were included in this study. Among them, there were 64 cases (32.2%) in the iICT group, 135 cases (67.8%) in the iCT group. There was a statistically significant difference in objective response rate (73.5% vs 48.9%) and conversion surgery rate (81.3% vs 66.7%), between the iICT and iCT groups (P=0.001 and P=0.019). Among the two groups of patients who underwent surgery, there were statistically significant differences in R0 resection rate (94.2% vs 82.2%) and pathological complete remission rate (23.1% vs 6.7%) between the iICT and iCT groups (P=0.043 and P=0.004). And there was no statistically significant difference in the incidence of grade 3 and above between two groups (P=0.928). The 2-year EFS of the iICT group and iCT group were 76.4% and 42.4%, respectively, with statistically significant differences (P=0.006). Conclusions Compared with simple chemotherapy, the combination of PD-1 inhibitors and chemotherapy can achieve better conversion surgery rate, tumor response and event-free survival in the conversion therapy of locally advanced unresectable ESCC.